2016
DOI: 10.4028/www.scientific.net/amm.819.541
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Analysis of Building Energy Efficiency Using Artificial Neural Network and Design of Experiments

Abstract: Energy consumption of buildings is increasing steadily and occupying approximately 30-40% of total energy use. It is important to predict heating and cooling loads of a building in the initial stage of design to find out optimal solutions among various design options, as well as in the operating stage after the building has been completed for energy efficient operation. In this paper, an artificial neural network model has been developed to predict heating and cooling loads of a building based on simulation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Artificial Neural Networks (ANN) [2,[9][10][11][12][13][14][15][16][17][18][19]] Decision Trees (DT) [20] Support Vector Regression (SVR) [11,13,14,19,[21][22][23]] Random Forest (RF) and Trees Ensemble [8,13,14,[20][21][22][23][24][25][26][27][28][29] Multi-Layer Perceptron (MLP) [14,20,23,27] Gaussian Mixture Model (GMM) [30] Gradient Boosted Regression Trees (GBRT) [24,31] Extreme Learning Machine (ELM) [10,32,33] Linear Regression (LR) [10,13,21,23,27,34,35] Radial Basis ...…”
Section: Machine Learning Techniques Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial Neural Networks (ANN) [2,[9][10][11][12][13][14][15][16][17][18][19]] Decision Trees (DT) [20] Support Vector Regression (SVR) [11,13,14,19,[21][22][23]] Random Forest (RF) and Trees Ensemble [8,13,14,[20][21][22][23][24][25][26][27][28][29] Multi-Layer Perceptron (MLP) [14,20,23,27] Gaussian Mixture Model (GMM) [30] Gradient Boosted Regression Trees (GBRT) [24,31] Extreme Learning Machine (ELM) [10,32,33] Linear Regression (LR) [10,13,21,23,27,34,35] Radial Basis ...…”
Section: Machine Learning Techniques Papersmentioning
confidence: 99%
“…In reference [18], the considered variables are (surface area, wall area, roof area, overall height, glazing area), while reference [35] uses (relative compactness, surface area, wall area, overall height, glazing area) to model the cooling problem. The importance of each variable is studied in [9] using ANOVA with the result of (relative compactness, surface area, wall area, overall height, glazing area) and (relative compactness, wall area, roof area, overall height, glazing area) as the most important variables for the heating and cooling problems, respectively.…”
Section: Reduced Models-separated Models By Number Of Floorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heating load (HL) and cooling load (CL) contribute around 30-40% of building's energy usage. Minimizing the HL and CL plays a major role in ensuring total energy consumption reduction in buildings [2]. Previous research in building energy based on computer experiment is done to optimize parameters for energy efficiency improvement in the residential or commercial buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in computer simulation of energy consumption have been conducted using random forest algorithm (RF) [3], support vector machine (SVM), polynomial regression, decision trees, artificial neural network (ANN) [2], genetic programming (GP) [4], support vector regression (SVR) with ANN [5] and multilayer perceptron (MLP) with grid search strategy algorithm [6]. Major study in energy building efficiency by T.Sanas and Xifara (2012) identified that RF hugely outperformed IRLS in finding an accurate functional relationship between the input and output variable.…”
Section: Introductionmentioning
confidence: 99%